A family of oligo(p‐phenylenevinylene) derivative aggregation‐induced emission probes: Ultrasensitive, rapid, and anti‐interfering fluorescent sensing of perchlorate via precise alkyl chain length modulation. Issue 2 (28th August 2022) - Xiao, Fangfang; Li, Yushu; Li, Jiguang; Lei, Da; Wang, Guangfa; Zhang, Tianshi; Hu, Xiaoyun; Dou, Xincun
Abstract: The precise regulation of interactions provided by aggregation‐induced emission (AIE) probes is of considerable significance for improving the sensing performance in the field of on‐site detection. Here, a highly sensitive perchlorate detection probe was designed by precisely modulating the van der Waals interactions by adjusting the length of the alkyl chain. The optimized AIE probe demonstrated superior perchlorate detection performance owing to its strong van der Waals interactions with perchlorate, including a low detection limit (53.81 nM), rapid response (<5 s), and excellent specificity even in the presence of 16 interfering anions. In addition, a hydrogel‐based device loaded with the probe was constructed to achieve ultrasensitive recognition of perchlorate particles with a detection limit as low as 15 fg under a fluorescence microscope. Moreover, the practicality of the probe was further verified by employing a sensing chip in a portable detector, and thus the probe has been proven to be highly promising for trace perchlorate monitoring in real scenarios. We expect the present study to be of great value for the efficient design of high‐performance fluorescent probes. Abstract : A novel strategy is proposed to boost the sensitivity of aggregation‐induced emission (AIE) probe by regulating van der Waals interactions between the probe and perchlorate through optimizing the alkyl chain length. The present strategy is a promising candidate for detecting trace hazardous substances and AIE‐based functional material conceptualization.